Pelatihan Menulis Puisi Pada Siswa Madrasah Tsanawiyah - Istianingrum, Rika; Wulansari, Lusiana; Alifah, Siti; Nurisman, Husain (Yayasan Daarul Huda Kruengmane, 2024)
The purpose of this community service activity is to provide training in writing poetry properly and correctly. The activity was attended by 21 junior high school students in West Java. The activity was carried out online from January to February 2021. The activity method used lecture and practice methods. Students were given reading materials and invited to see directly some natural atmospheres and understand poetry writing. The results of the activity produced poetry and several short stories that will be published as a collection of poetry books with the theme of life and nature.